Pengembangan produk puding karakter lucu: inovasi, distribusi, dan analisis kelayakan usaha - yasmin, hawa arini dina (Maliki Interdisciplinary Journal, 2025)
This study aims to examine how innovations in design and materials can increase the selling value of character pudding products, identify the main challenges in production and distribution, and analyze the costs and benefits in developing this business. The research method used was a descriptive qualitative approach with observation and documentation as data collection techniques. The results showed that design innovations such as the use of popular characters and high-quality materials were able to increase consumer buying interest. The main challenges faced are product shape consistency, durability during distribution, and production cost efficiency. From a financial perspective, the character pudding business has good profit potential if managed with effective marketing strategies and proper cost control. This research contributes to understanding the dynamics of creative culinary businesses, especially among MSME players.